Capital reserve calculation analysis of operational risk in submarine cable service portfolio - Kusumawardhani, Febriyati; Hanggraeni, Dewi (Universitas Wiralodra, 2024)
This study analyzes the amount of capital reserves required for the Submarine Cable Service PT AAA to mitigate the risk of delays in completing work without disrupting the company's cash flow. Data used in this paper is the operational loss of delay work in the Submarine Cable Service portfolio from 2016 to 2019. The method and analysis used in this paper are the Monte Carlo simulation to calculate Operation Risk Variance (OpVar) by analyzing the distribution of severity and frequency. The result of the study shows that delayed work is the risk that has the most influence on the company's cash flow. PT AAA needs Rp 2.16 billion per event as capital reserve PT AAA to mitigate the risk of work delays in the Submarine Cable Service portfolio. Risk mitigation needs to minimize the potential loss are choosing the right partner in the operational process, scheduling the cable repair process, and securing the amount of capital reserve that has been counted.